XRCC1 632 as a candidate for cancer predisposition via a complex interaction with genetic variants of base excision repair and double strand break repair genes - Singh, Amrita; Singh, Navneet; Behera, Digambar; Sharma, Siddharth (Future oncology (London, England), 2019)
The DNA repair system safeguards integrity of DNA. Genetic alterations force the improper repair which in conjugation with other factors ultimately results in carcinogenesis. PCR-restriction fragment length polymorphism was used for genotyping, which was followed by statistical analysis using logistic regression analysis, multifactor dimensionality reduction and classification and regression analysis tree, elaborating the association with lung cancer subjects. Combination of and showcased a high risk of eightfold (odds ratio: 7.92; 95% CI: 2.68–23.4; p = 0.0002; false discovery rate (FDR) p = 0.002). Similarly, and (odds ratio: 5.07; 95% CI: 2.6–9.67; p < 0.0001; FDRp = 0.002) had a high risk. Multifactor dimensionality reduction analysis revealed five factor model as the best model with prediction error of 0.37 (p = 0.02). There was a clear indication that high order interactions were major role players in the study.